Socioeconomic and labor characterization and prevalence of chronic disease in the Colombian population in the periods 2010, 2013, and 2016: A multiple correspondence analysis - Francisco Palencia-Sánchez; Gustavo Antonio Bruges Morales; Martha Riaño-Casallas (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: To analyze the relationship between the prevalence of chronic diseases and socioeconomic, demographic and occupational determinants in the Colombian population in 2010, 2013 and 2016. We sought to identify patterns of association between these variables and evaluate how they have evolved over time, with a particular emphasis on the implications for public health, especially in informal work contexts. Methods: We used longitudinal data from the Colombian Longitudinal Urban Survey, which covers socioeconomic strata 1 to 4. The sample includes both men and women and heads of households and spouses, aged 18 to 65 years. The variables of interest are classified into three categories: health, labor and sociodemographic factors. The main methodology used was Multiple Correspondence Analysis (MCA). Results: Three different labor groups were identified in the sample: formal, semi-formal and informal. The informal workers group showed a higher prevalence of chronic diseases compared to the other two groups. Labor category was the social determinant of greatest relevance in health variability. Conclusion: The study’s findings indicate that labor informality is associated with an elevated risk of developing chronic diseases in Colombia. These results highlight the necessity for policy interventions that prioritize enhancing working conditions as a strategy to achieve improved public health outcomes.